2005
DOI: 10.1161/01.hyp.0000154680.44184.01
|View full text |Cite
|
Sign up to set email alerts
|

Different Involvement of Extracellular Matrix Components in Small and Large Arteries During Chronic NO Synthase Inhibition

Abstract: Abstract-In essential hypertension, conduit arteries present hypertrophic remodeling (increased cross-sectional area), whereas small arteries undergo eutrophic remodeling. The involvement of matrix metalloproteinases (MMPs) and de-adhesion proteins, such as tenascin-C and thrombospondin, has been relatively well characterized in large artery remodeling, but their contribution is not known in small artery remodeling. Rats received N -nitro-L-arginine methyl ester (L-NAME; 50 mg/kg per day) in their drinking wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 46 publications
6
48
0
9
Order By: Relevance
“…12,13,[28][29][30] While there is evidence that MMPs in erectile dysfunction JJ Muniz et al patients with ED are more likely to have the vascular alterations commonly found in cardiovascular diseases, 2,4-9 especially among diabetics, 4-6,10,11 our findings showed similar net MMP-2 and MMP-9 activities in ED patients and in healthy controls, thus suggesting that these enzymes may not be involved in ED. Importantly, MMPs levels were carefully assessed by two independent, different techniques in the present study, thus minimizing the probability of analytical limitations.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…12,13,[28][29][30] While there is evidence that MMPs in erectile dysfunction JJ Muniz et al patients with ED are more likely to have the vascular alterations commonly found in cardiovascular diseases, 2,4-9 especially among diabetics, 4-6,10,11 our findings showed similar net MMP-2 and MMP-9 activities in ED patients and in healthy controls, thus suggesting that these enzymes may not be involved in ED. Importantly, MMPs levels were carefully assessed by two independent, different techniques in the present study, thus minimizing the probability of analytical limitations.…”
Section: Discussionmentioning
confidence: 41%
“…Imbalanced MMPs activities have been implicated in many clinical cardiovascular diseases, [12][13][14][15][16][17][18]27 and the use of MMPs inhibitors has been suggested as a relevant pharmacological target, especially to prevent the vascular alterations associated with these conditions. 12,13,[28][29][30] While there is evidence that MMPs in erectile dysfunction JJ Muniz et al patients with ED are more likely to have the vascular alterations commonly found in cardiovascular diseases, 2,4-9 especially among diabetics, 4-6,10,11 our findings showed similar net MMP-2 and MMP-9 activities in ED patients and in healthy controls, thus suggesting that these enzymes may not be involved in ED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond cell culture, limiting NO for 28 days in male rats by daily feeding of L-NAME in the drinking water was associated with increased TSP1 protein expression in distal mesenteric arteries and elevated blood pressure (17). In a small clinical study, 4 weeks of aerobic training in healthy young men was associated with increased eNOS protein expression in vastus lateralis muscle samples.…”
Section: E No Regulation Of Tsp1 Expressionmentioning
confidence: 97%